Activation of Toll Immune Pathway in an Insect Vector Induced by a Plant Virus - He, Yu-Juan; Lu, Gang; Qi, Yu-Hua; Zhang, Yan; Zhang, Xiao-Di; Huang, Hai-Jian; Zhuo, Ji-Chong; Sun, Zong-Tao; Yan, Fei; Chen, Jian-Ping; Zhang, Chuan-Xi; Li, Jun-Min (Frontiers in Immunology, 2021)
The Toll pathway plays an important role in defense against infection of various pathogenic microorganisms, including viruses. However, current understanding of Toll pathway was mainly restricted in mammal and some model insects such as Drosophila and mosquitoes. Whether plant viruses can also activate the Toll signaling pathway in vector insects is still unknown. In this study, using rice stripe virus (RSV) and its insect vector (small brown planthopper, Laodelphax striatellus) as a model, we found that the Toll pathway was activated upon RSV infection. In comparison of viruliferous and non-viruliferous planthoppers, we found that four Toll pathway core genes (Toll, Tube, MyD88, and Dorsal) were upregulated in viruliferous planthoppers. When the planthoppers infected with RSV, the expressions of Toll and MyD88 were rapidly upregulated at the early stage (1 and 3 days post infection), whereas Dorsal was upregulated at the late stage (9 days post infection). Furthermore, induction of Toll pathway was initiated by interaction between a Toll receptor and RSV nucleocapsid protein (NP). Knockdown of Toll increased the proliferation of RSV in vector insect, and the dsToll-treated insects exhibited higher mortality than that of dsGFP-treated ones. Our results provide the first evidence that the Toll signaling pathway of an insect vector is potentially activated through the direct interaction between Toll receptor and a protein encoded by a plant virus, indicating that Toll immune pathway is an important strategy against plant virus infection in an insect vector.